Utilization and Dose Optimization of Angiotensin-Converting Enzyme Inhibitors among Heart Failure Patients in Southwest Ethiopia - Angamo, Mulugeta Tarekegn; Gidey, Kidu; Kumela Goro, Kabaye; Niriayo, Yirga Legesse (BioMed research international, 2019)
Background. Optimal use of angiotensin-converting enzyme inhibitors (ACEIs) is crucial to improve the treatment outcome in heart failure patients. However, little is known about the optimal use of ACEIs among heart failure patients in our setting. Therefore, our study aimed to investigate the utilization and optimal dosing of ACEIs and associated factors in heart failure patients. Method. A cross-sectional study was conducted on randomly selected patients with heart failure between February 2016 and June 2016 at ambulatory care clinic of Jimma University Medical Center, Ethiopia. Data were collected through patient interview and review of medical records. Binary logistic regression analysis was done to identify factors associated with utilization and optimal dosing of ACEIs. Results. A total of 308 patients were included in the final analysis of this study. The mean (±standard deviation) age of the patients was 52.3 ±15.5 years. Out of the total, 74.7% of the patients were receiving ACEIs. Among the patients who were receiving ACEIs, only 35.7% were taking optimal dose. New York Heart Association (NYHA) class III (Adjusted odds ratio (AOR):0.12, 95% confidence interval (CI):0.02–0.98), valvular heart disease (AOR: 0.27, 95% CI: 0.13-0.56), hypertension (AOR: 5.82, 95% CI: 2.16-15.71), and diabetes mellitus (AOR: 3.84, 95% CI: 1.07-13.86) were significantly associated with the use of ACEIs, whereas age ≥65 (AOR: 2.61, 95%CI: 1.20-5.64), previous hospitalization for heart failure (AOR: 2.08, 95%CI: 1.11-3.92), diuretic use (AOR: 5.60, 95%CI: 2.75-11.40), and dose of furosemide >40mg (AOR: 9.80, 95%CI: 3.00-31.98) were predictors of suboptimal dosing of ACEIs. Conclusion. Although majority of patients were receiving ACEIs, only about one-third were using optimal dosage. Valvular heart disease and NYHA class III were negatively associated with the use of ACEIs while previous hospitalization for heart failure, old age, diuretic use, and diuretic dose were predictors of suboptimal dosing of ACEIs. Therefore, more effort needs to be done to minimize the potentially modifiable risk factors of suboptimal use of ACEIs therapy in heart failure patients.